Fair value reclassifications of financial assets during the financial crisis - Jannis Bischof; Ulf Brüggemann; Holger Daske (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
At the peak of the financial crisis in October 2008, the IASB amended IAS 39 to grant companies the option of abandoning fair value recognition for selected financial assets. Using a comprehensive global sample of publicly listed IFRS banks, we find that banks use the reclassification option to forgo the recognition of fair value losses and ultimately the regulatory costs of supervisory intervention. Analyses of stock market reactions suggest that a small subset of the most troubled banks benefit from such reclassifications. However, analyses of related footnote disclosures reveal that two-thirds of reclassifying banks do not fully comply with the accompanying IFRS 7 requirements. These banks experience a significant increase in bid-ask spreads in the long run.
Keywords: G14; G21; G28; M41; M48; 330; bank regulation; fair value accounting; financial crisis; IAS 39; IFRS 7; Bankbilanz; International Financial Reporting Standards; Fair-Value-Bewertung; Bilanzpolitik; Bankenaufsicht; Bankenkrise; Finanzmarktkrise; Welt